Social Media and Digital Literacy on Cryptocurrency Trust: The Moderating Role of Financial Literacy - Tobing, Clairine Cardin; Maria Asumpta Evi Marlina (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
The development of digital assets has driven an increase in interest among the younger generation to invest in cryptocurrency, but their level of trust varies and is influenced by the quality of information and digital literacy skills. This study aims to analyze the influence of social media and digital literacy on cryptocurrency investment trust, with financial literacy as a moderating variable. Data was collected through a Google Form questionnaire distributed to members of the Telegram group “INDODAX– Indonesia Bitcoin & Crypto Exchange Official Group” with a population of 46,302 members, and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach. The results show that social media does not have a significant effect on investment confidence, while digital literacy has a positive and significant effect. Financial literacy acts as a moderating variable that weakens the influence of social media but strengthens the influence of digital literacy on cryptocurrency investment confidence. The implications of this